The Annual Intensive Course on Medical Ethics (Journal of medical ethics, 2000)
The Annual Intensive Course on Medical Ethics will be held from 11 - 15 September, 2000 at the Wolfson Conference Centre, Imperial College Hammersmith Hospital Campus, London. The course …